Multifunctional flame retardant and application thereof in epoxy resin

By preparing a multifunctional flame retardant, the problems of poor dispersion uniformity and decreased light transmittance of the phosphorus-nitrogen-silicon flame retardant system in epoxy resin were solved, achieving high-efficiency flame retardancy and ultraviolet shielding effects for epoxy resin.

CN120965913APending Publication Date: 2025-11-18CHANGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511016699.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-23
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

The existing phosphorus-nitrogen-silicon flame retardant system has poor dispersion uniformity in the polymer matrix, resulting in a decrease in light transmittance. Furthermore, the introduction of flame retardants affects the transparency and impact resistance of epoxy resins.

Method used

A Schiff base structure is formed by the nucleophilic substitution reaction of tert-butyldimethylchlorosilane with eugenol, followed by a condensation reaction with an amino compound and an organophosphorus reagent to prepare a multifunctional flame retardant, which is then applied to epoxy resin composites.

Benefits of technology

It significantly improves the flame retardant performance of epoxy resin, maintains the transparency of the material, and endows it with excellent fire resistance and ultraviolet shielding function, solving the problems of uniform dispersion of flame retardants and decreased light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120965913A_ABST
    Figure CN120965913A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of flame-retardant composite materials, and particularly relates to a multifunctional flame retardant and application thereof in epoxy resin. The method comprises the following steps: firstly, carrying out nucleophilic substitution reaction on tert-butyldimethylsilyl chloride and syringaldehyde to obtain a primary intermediate product; carrying out condensation reaction on the primary intermediate product and an amino-containing compound to form a secondary intermediate product with a Schiff base structure; and finally, carrying out addition reaction on the secondary intermediate product and a specific phosphorus-containing reagent to successfully prepare the target flame retardant. Researches show that the flame retardant is remarkable in efficiency, can effectively improve the limit oxygen index (LOI value) and the vertical combustion test (such as UL-94) grade of a material after being applied to an epoxy resin system, and endows the composite material with excellent light transmission, anti-dripping performance and good ultraviolet shielding characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flame-retardant composite materials, specifically relating to a multifunctional flame retardant and its application in epoxy resin. Background Technology

[0002] Epoxy resin (EP), as a typical representative of thermosetting polymer materials, has become an indispensable key material in fields such as electronic packaging, aerospace, and transportation due to its outstanding mechanical properties, excellent electrical insulation characteristics, and good chemical corrosion resistance. However, this material has revealed significant fire safety hazards during application: cured EP composite materials are extremely flammable, releasing large amounts of toxic fumes during combustion and producing severe dripping, accelerating the spread of fire. At the same time, EP's inherent brittleness and poor impact resistance also severely restrict its widespread application in high-end fields.

[0003] To address the aforementioned issues, the phosphorus-nitrogen-silicon ternary synergistic flame retardant system exhibits unique advantages. This system organically integrates the high-efficiency flame retardant properties of phosphorus-based flame retardants, the low-toxicity and environmentally friendly advantages of nitrogen-based flame retardants, and the high-temperature resistance of silicon-based flame retardants. This not only significantly improves the flame retardant performance of polymer materials but also substantially reduces the environmental and human health hazards during combustion. However, it is worth noting that while existing phosphorus-nitrogen-silicon flame retardant systems meet relevant standards in terms of flame retardancy, they still face significant technical bottlenecks. These bottlenecks primarily manifest as poor uniformity of flame retardant dispersion in the polymer matrix and the tendency for the introduction of flame retardants to lead to a significant decrease in the light transmittance of originally transparent polymer materials. Summary of the Invention

[0004] To address the technical problems identified in the background section, this invention proposes a multifunctional flame retardant and its application in epoxy resins. The core of this technical solution lies in: firstly, constructing a silicon-containing structural unit through a nucleophilic substitution reaction of tert-butyldimethylchlorosilane and eugenol; subsequently, undergoing a condensation reaction with an amino compound to form a Schiff base structure; and finally, undergoing an addition reaction with a phosphorus-containing reagent to prepare a multifunctional flame retardant with a synergistic flame-retardant effect. More specifically, this invention also applies this flame retardant to the modification of epoxy resin composite materials.

[0005] To achieve the above technical objectives, the technical solution of this invention adopts the following technical approach.

[0006] The preparation method of the multifunctional flame retardant specifically includes the following steps: (1) Syringaldehyde undergoes a nucleophilic substitution reaction with tert-butyldimethylchlorosilane to prepare a primary intermediate; At 20–25°C, eugenol and triethylamine were added to tetrahydrofuran and stirred continuously until completely dissolved to obtain solution 1. Separately, tert-butyldimethylchlorosilane was added to tetrahydrofuran to achieve homogeneous miscibility, yielding solution 2. Under a nitrogen atmosphere, solution 2 was added dropwise to the reaction system of solution 1 at a uniform rate. After the dropping program was terminated, the oil bath temperature was increased to 65–70°C using a gradient heating mode, and the reaction was maintained at this temperature for 10–12 hours under isothermal conditions.

[0007] The molar ratio of eugenol, triethylamine and tert-butyldimethylchlorosilane is 0.05-0.1:0.05-0.01:0.05-0.1, and the dropping rate is controlled so that the feeding process takes 30 to 60 minutes.

[0008] After the reaction was terminated, the cooling water circulation and nitrogen supply were stopped, and the system was allowed to cool naturally to room temperature. The generated triethylamine hydrochloride byproduct was removed using a vacuum filtration apparatus connected to a Buchner funnel. The filtrate was collected and transferred to an extraction vessel, and excess deionized water was added for liquid-liquid extraction. After vigorous shaking, the mixture was allowed to stand and separate into layers. The lower organic phase was separated, and the extraction-phase separation operation was repeated three times each to complete the washing. The purified organic phase was transferred to a rotary evaporator and concentrated under reduced pressure at 70°C. After removing the solvent, the residue was placed in a beaker and transferred to a vacuum drying oven for dehydration at 65°C for 12 hours, finally yielding a pale yellow solid primary intermediate (named STL). This product was ground into a uniform powder and stored in a sealed container for later use.

[0009] (2) The primary intermediate reacts with an amino compound via a Schiff base reaction to synthesize a secondary intermediate; The primary intermediate obtained in step (1) was dehydrated overnight. The dehydrated STL intermediate was then dissolved in anhydrous ethanol and stirred continuously at ambient temperature until the STL was completely dissolved. Anamine compound was added to anhydrous ethanol to form a homogeneous solution, which was then poured into the STL intermediate solution in one go. The system was gradually heated to 60–70°C using a programmed temperature control method. A vertical reflux condenser was installed, and the reaction was maintained at the set temperature for 20 to 24 hours.

[0010] The amino compound is 4,4'-diaminodiphenyl sulfone, chitosan, or p-phenylenediamine.

[0011] The molar ratio of primary intermediates to amine compounds is 0.07-0.14:0.5-1.

[0012] After the reaction was complete, the condensation system was first stopped, and the reaction system was allowed to cool naturally to 25°C. A Buchner funnel combined with a vacuum filtration device was used to separate the solid and liquid phases of the mixture, and the precipitate was collected. Anhydrous ethanol and deionized water were used as washing solvents, and the precipitate was purified by alternating washing three times to effectively remove residual impurities. The purified solid was transferred to a clean beaker and placed in a vacuum drying apparatus for dehydration at a constant temperature of 60°C for 12 hours, finally obtaining a yellow crystalline secondary intermediate product (named STLC). This product was finely ground into a uniform powder and stored in a desiccator for later use.

[0013] (3) The secondary intermediate product undergoes an addition reaction with an organophosphorus reagent to obtain the target product; First, the organophosphorus reagent was dissolved in anhydrous ethanol to form a homogeneous solution. The STLC intermediate was dissolved in anhydrous ethanol and stirred at room temperature until completely dissolved. Then, the organophosphorus reagent ethanol solution was quantitatively transferred to the reaction system. The reaction temperature was stabilized within the range of 90–100°C using a temperature program. A vertical reflux condenser was installed, and the reaction was continued for 6 to 8 hours to complete the reaction.

[0014] The organophosphorus reagents are: diethyl phosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) or diphenyl phosphate.

[0015] The molar ratio of organophosphorus reagent to STLC is 0.1-0.2:0.05-0.1.

[0016] After the reaction was complete, the cooling water supply was first cut off, and the reaction system was allowed to cool naturally to 25°C. Solid-liquid separation was achieved using a Buchner funnel connected to a vacuum filtration system, and the target precipitate was collected. The product was purified by three alternating washing steps using anhydrous ethanol and deionized water as washing solvents, effectively removing unreacted raw materials and byproducts. The purified solid was transferred to a clean container and placed in a vacuum drying apparatus for dehydration at a constant temperature of 60°C for 12 hours, finally obtaining a pale green solid final product (named STLCP). Structural characterization confirmed that this substance is a novel phosphorus-nitrogen-silicon synergistic flame retardant. The product was finely ground into a uniform powder and stored in a desiccator away from light for later use.

[0017] The multifunctional flame retardant prepared by the above method is used for flame retardant modification of epoxy resin.

[0018] The steps for flame-retardant modification of epoxy resin are as follows: (a) Preheat the epoxy resin to a molten state to form a uniform epoxy resin solution; add the multifunctional flame retardant prepared above to the epoxy resin solution and stir until completely dispersed; (b) After adding the curing agent to step (a), continue stirring to form a homogeneous mixture; (c) After injecting the mixture into the preheated mold, place it in a vacuum drying oven to complete the curing process and obtain flame-retardant modified epoxy resin.

[0019] The flame retardant in the epoxy resin has a mass percentage of 1-6 wt%; the stirring time is not less than 120 minutes; the curing agent is 4,4'-diaminodiphenylmethane, and its addition amount is 25% of the mass of the epoxy resin.

[0020] The beneficial effects of this invention are as follows: The novel multifunctional flame retardant synthesized in this invention exhibits significant multi-phase synergistic flame retardant properties. Its unique two-phase mechanism (including gas-phase barrier and condensed-phase charring) achieves excellent fire resistance. Experiments show that when applied to epoxy resin systems, this additive not only significantly improves the oxygen index of the material and achieves a UL-94 vertical burning test rating, but also maintains the original optical transparency of the matrix. Furthermore, this technology successfully solves the problem of molten droplets during polymer combustion and imparts excellent UV shielding properties to the substrate. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the synthesis route of the multifunctional flame retardant of the present invention.

[0022] Figure 2 The FTIR spectra of the raw materials, intermediates, and flame retardant STLCP in Example 1 are shown.

[0023] Figure 3 The SEM (left) and EDS (right) images of the raw materials, intermediates, and flame retardant STLCP in Example 1 are shown.

[0024] Figure 4 Digital images of the epoxy resin composite materials obtained in the examples and comparative examples are shown.

[0025] Figure 5 The graphs show the UL-94 and LOI test results of the epoxy resin composites obtained in the examples and comparative examples.

[0026] Figure 6 The results of UV absorbance analysis of the epoxy resin composites obtained in Examples 1-3 and Comparative Examples 1-3 are shown. Detailed Implementation

[0027] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments.

[0028] Raw materials: eugenol, tert-butyldimethylchlorosilane; amino compounds: chitosan, 4,4'-diaminodiphenyl sulfone, p-phenylenediamine; organophosphorus reagents: diethyl phosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) or diphenyl phosphate; auxiliary reagents: triethylamine, tetrahydrofuran, deionized water, anhydrous ethanol, all commercially available; all raw materials must be dried and sealed before use. Example 1

[0029] 0.05 mol (9.1 g) of eugenol, 0.05 mol (5.06 g) of triethylamine, and 100 ml of tetrahydrofuran were added to a three-necked flask equipped with a magnetic stirrer and placed in a constant-temperature oil bath (25°C). The mixture was stirred continuously until completely dissolved. Separately, 0.05 mol (7.54 g) of tert-butyldimethylchlorosilane was placed in a container, and 20 ml of tetrahydrofuran was added and stirred to achieve homogeneous miscibility. Under a nitrogen atmosphere, the tert-butyldimethylchlorosilane solution was introduced into the three-necked flask through a constant-pressure dropping funnel, and the dropping rate was controlled so that the addition process took 0.5 h. After the dropping program was terminated, the oil bath temperature was increased to 65°C using a gradient heating mode, and the reaction was maintained at this temperature for 12 hours.

[0030] After the reaction was terminated, the cooling water circulation and nitrogen supply were stopped, and the system was allowed to cool naturally to room temperature. The generated triethylamine hydrochloride byproduct was removed using a vacuum filtration apparatus connected to a Buchner funnel. The filtrate was collected and transferred to an extraction vessel, and excess deionized water was added for extraction. The mixture was allowed to stand and separate into layers. The lower organic phase was separated, and the extraction-phase separation-extraction-phase separation-extraction-phase separation operation was repeated to complete the washing. The purified organic phase was transferred to a rotary evaporator flask and concentrated under reduced pressure at 70°C. After removing the solvent, the residue was placed in a beaker and transferred to a vacuum drying oven for dehydration at 65°C for 12 hours, finally yielding a pale yellow solid primary intermediate (named STL). This product was ground into a uniform powder and stored in a sealed container for later use.

[0031] The aforementioned primary intermediate was placed in a drying oven for overnight dehydration. 0.07 mol (20.74 g) of the dehydrated STL and 150 ml of anhydrous ethanol were added to a three-necked flask and transferred to a constant-temperature oil bath equipped with an electromagnetic stirrer. Stirring was continued at ambient temperature until the STL was completely dissolved. 0.5 mol (8.1 g) of chitosan was accurately weighed and placed in a container, and anhydrous ethanol was added to form a homogeneous solution. This homogeneous solution was then poured into the three-necked flask in one go. The system was gradually heated to 70°C using a programmed temperature control method. A vertical reflux condenser was installed, and the reaction was maintained at the set temperature for 24 hours.

[0032] After the reaction was complete, the condensation system was stopped, and the reaction system was allowed to cool naturally to 25°C. A Buchner funnel combined with a vacuum filtration device was used to separate the solid and liquid phases of the mixture, and the precipitate was collected. The precipitate was purified by washing three times each with anhydrous ethanol and deionized water, effectively removing residual impurities. The purified solid was transferred to a clean beaker and placed in a vacuum drying apparatus for dehydration at a constant temperature of 60°C for 12 hours, finally obtaining a yellow crystalline secondary intermediate (named STLC). This product was finely ground into a uniform powder and stored in a desiccator for later use.

[0033] 0.1 mol (21.62 g) of DOPO was dissolved in anhydrous ethanol to form a homogeneous solution. 0.05 mol (21.41 g) of STLC and 150 mL of anhydrous ethanol were added to a three-necked round-bottom flask, which was then placed in a magnetically stirred temperature-controlled bath and stirred at room temperature until completely dissolved. The ethanol solution of DOPO was then transferred to the reaction system. The reaction temperature was stabilized at 95 °C using a temperature program. A vertical reflux condenser was installed, and the reaction was continued for 6 hours to complete the conversion.

[0034] After the reaction was complete, the cooling water supply was cut off, and the reaction system was allowed to cool naturally to 25°C. Solid-liquid separation was achieved using a Buchner funnel connected to a vacuum filtration system, and the target precipitate was collected. The product was washed three times each with anhydrous ethanol and deionized water as washing solvents to effectively remove unreacted raw materials and byproducts. The purified solid was transferred to a clean container and placed in a vacuum drying apparatus for dehydration at a constant temperature of 60°C for 12 hours, finally obtaining a pale green solid final product (named STLCP). Structural characterization confirmed that this substance is a novel phosphorus-nitrogen-silicon synergistic flame retardant. The product was finely ground to form a uniform powder and stored in a desiccator away from light for later use.

[0035] The chemical structure of STLCP was analyzed using FT-IR, and the results are as follows: Figure 2 As shown, in Figure 2 Syringaldehyde in the text refers to syringaldehyde. Figure 2 This demonstrates that the synthesis of STL and STLC was successful, and syringaldehyde was obtained at 3289 cm⁻¹. -1 There is a distinct broadband band at 1672 cm⁻¹, corresponding to the characteristic signal peak of the -OH group. For STL, the -OH characteristic peak disappears significantly, indicating that syringaldehyde and tert-butyldimethylchlorosilane are linked together via a substitution reaction. -1The characteristic peak at 1620 cm⁻¹ is attributed to the -CHO group in the syringaldehyde structure. This phenomenon is also clearly observed in STL, indicating that the reaction of the primary intermediate STL was successful. In the case of STLC, introducing CS into STL induces a Schiff base reaction, thereby weakening the intensity of the -CHO peak. In the STLC spectrum, the -CHO signal characteristic peak clearly disappears, replaced by a peak at 1620 cm⁻¹. -1 The characteristic -C=N signal peak is observed at [location missing]. In STLCP, the -C=N signal peak disappears, indicating that STLC undergoes a nucleophilic addition reaction with DOPO. [At 1387 cm⁻¹] -1 A new characteristic absorption peak appeared, attributed to the stretching vibration of -PC, further demonstrating the success of the introduction of the phenanthrene group. Preliminary results indicate that the synthesis of the novel phosphorus-nitrogen-silicon flame retardant STLCP is successful. Figure 3 As shown, SEM and EDS tests were performed on STLCP to further analyze its morphology and elemental distribution. The microstructure of STLCP is a bulk structure. C, O, P, and Si elements are uniformly distributed on its surface. In summary, these results further confirm the structure and elemental composition of STLCP, indicating that STLCP was successfully prepared, which corresponds to the FTIR results mentioned above.

[0036] Preparation of flame-retardant epoxy resin composite materials: 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 0.3g of flame retardant STLCP were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Example 2

[0037] The preparation of primary intermediates, secondary intermediates, and STLCP is the same as in Example 1.

[0038] Preparation of flame-retardant epoxy resin composite materials: 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 0.9g of flame retardant STLCP were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Example 3

[0039] The preparation of primary intermediates, secondary intermediates, and STLCP is the same as in Example 1.

[0040] Preparation of flame-retardant epoxy resin composite materials: 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 1.8g of flame retardant STLCP were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Example 4

[0041] Preparation of primary intermediate products: Same as in Example 1.

[0042] The aforementioned primary intermediate was placed in a drying oven for overnight dehydration. 0.07 mol (20.74 g) of STL and 150 ml of anhydrous ethanol were added sequentially to a three-necked reactor, then transferred to a constant-temperature oil bath equipped with an electromagnetic stirrer. Stirring was continued at ambient temperature until the STL was completely dissolved. 8.1 g of 4,4'-diaminodiphenyl sulfone was accurately weighed and placed in a container, and anhydrous ethanol was added to form a homogeneous solution. This homogeneous solution was then poured into the reactor in one go. The system was gradually heated to 70°C using a programmed temperature control method. A vertical reflux condenser was installed, and the reaction was maintained at the set temperature for 24 hours.

[0043] The post-processing of the secondary intermediate is the same as in Example 1.

[0044] First, 0.1 mol (21.62 g) of DOPO was dissolved in anhydrous ethanol to form a homogeneous solution. In a three-necked round-bottom flask, 0.05 mol (22.90 g) of the secondary intermediate and 150 mL of anhydrous ethanol were added, and the flask was placed in a magnetically stirred, temperature-controlled bath and stirred at room temperature until completely dissolved. Then, the ethanol solution of DOPO was quantitatively transferred to the reaction system. The reaction temperature was stabilized at 95 °C using a programmed temperature riser. A vertical reflux condenser was installed, and the reaction was continued for 6 hours to complete the conversion.

[0045] The post-treatment of the flame retardant is the same as in Example 1.

[0046] Preparation of flame-retardant epoxy resin composite materials: 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 1.8g of the flame retardant from Example 4 were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Example 5

[0047] The preparation of primary and secondary intermediate products is the same as in Example 1.

[0048] Dissolve 0.1 mol (25.01 g) of diphenyl phosphate in 20 mL of anhydrous ethanol in a beaker beforehand. Add 0.05 mol (21.41 g) of STLC and 150 mL of anhydrous ethanol to a three-necked flask, and place it in an oil bath with a magnetic stirrer at room temperature. Stir until the secondary intermediate is fully dissolved. Then dissolve the diphenyl phosphate in the ethanol solution and pour it into the three-necked flask. Raise the temperature to 95 °C. Set up a reflux condenser and react for 6 h.

[0049] The post-treatment of the flame retardant is the same as in Example 1.

[0050] Preparation of flame-retardant epoxy resin composite materials: 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 1.8g of the flame retardant from Example 5 were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Example 6

[0051] The preparation of the primary intermediate product is the same as in Example 1.

[0052] The aforementioned primary intermediate was placed in a drying oven for overnight dehydration. 0.07 mol (20.74 g) of the dehydrated STL and 150 ml of anhydrous ethanol were added to a three-necked flask and transferred to a constant-temperature oil bath equipped with an electromagnetic stirrer. Stirring was continued at ambient temperature until the STL was completely dissolved. 0.25 mol (4.05 g) of chitosan was accurately weighed and placed in a container, and anhydrous ethanol was added to form a homogeneous solution. This homogeneous solution was then poured into the three-necked flask in one go. The system was gradually heated to 70°C using a programmed temperature control method. A vertical reflux condenser was installed, and the reaction was maintained at the set temperature for 24 hours.

[0053] The post-processing of the secondary intermediate is the same as in Example 1.

[0054] 0.1 mol (21.62 g) of DOPO was dissolved in anhydrous ethanol to form a homogeneous solution. 0.05 mol (21.41 g) of the secondary intermediate and 150 mL of anhydrous ethanol were added to a three-necked round-bottom flask and placed in a magnetically stirred temperature-controlled bath. The mixture was stirred at room temperature until completely dissolved. The ethanol solution of DOPO was then transferred to the reaction system. The reaction temperature was stabilized at 95 °C using a temperature program. A vertical reflux condenser was installed, and the reaction was continued for 6 hours to complete the conversion.

[0055] The post-treatment of the flame retardant is the same as in Example 1.

[0056] Preparation of flame-retardant epoxy resin composite materials: 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 1.8g of the flame retardant from Example 6 were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Example 7

[0057] The preparation of the primary intermediate product is the same as in Example 1.

[0058] The aforementioned primary intermediate was placed in a drying oven for overnight dehydration. 0.07 mol (20.74 g) of the dehydrated STL and 150 ml of anhydrous ethanol were added to a three-necked flask and transferred to a constant-temperature oil bath equipped with an electromagnetic stirrer. Stirring was continued at ambient temperature until the STL was completely dissolved. 1 mol (16.2 g) of chitosan was accurately weighed and placed in a container, and anhydrous ethanol was added to form a homogeneous solution. This homogeneous solution was then poured into the three-necked flask in one go. The system was gradually heated to 70°C using a programmed temperature control method. A vertical reflux condenser was installed, and the reaction was maintained at the set temperature for 24 hours.

[0059] The post-processing of the secondary intermediate is the same as in Example 1.

[0060] 0.1 mol (21.62 g) of DOPO was dissolved in anhydrous ethanol to form a homogeneous solution. 0.05 mol (21.41 g) of STLC and 150 mL of anhydrous ethanol were added to a three-necked round-bottom flask, which was then placed in a magnetically stirred temperature-controlled bath and stirred at room temperature until completely dissolved. The ethanol solution of DOPO was then transferred to the reaction system. The reaction temperature was stabilized at 95 °C using a temperature program. A vertical reflux condenser was installed, and the reaction was continued for 6 hours to complete the conversion.

[0061] The post-treatment of the flame retardant is the same as in Example 1.

[0062] 30 g of bisphenol A diglycidyl ether, 7.5 g of curing agent 4,4'-diaminodiphenylmethane, and 1.8 g of flame retardant STLCP from Example 7 were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 min to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 h, then at 150°C for 2 h to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Example 8

[0063] The preparation of primary intermediates, secondary intermediates, and STLCP is the same as in Example 1.

[0064] Preparation of flame-retardant epoxy resin composite materials: 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 2.4g of flame retardant STLCP were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, followed by 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Comparative Example 1

[0065] The preparation process of epoxy resin composite materials includes the following steps: 30g of bisphenol A diglycidyl ether and 7.5g of curing agent 4,4'-diaminodiphenylmethane were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, and then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Comparative Example 2

[0066] The preparation process of epoxy resin composite materials includes the following steps: 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 1.8g of flame retardant DOPO were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold. Comparative Example 3

[0067] The preparation of primary and secondary intermediate products is the same as in Example 1.

[0068] Preparation of flame-retardant epoxy resin composite materials.

[0069] 30g of bisphenol A diglycidyl ether, 7.5g of curing agent 4,4'-diaminodiphenylmethane, and 1.8g of flame retardant STLC were mixed and completely dissolved. The mixture was then defoamed under vacuum for 30 minutes to remove air bubbles from the system. The resulting mixture was poured into a mold and kept at 100°C for 2 hours, then at 150°C for 2 hours to fully cure, yielding the composite material. Finally, the composite material was removed from the mold.

[0070] To illustrate the practical effects of the present invention, the composite materials of the embodiments and comparative examples were tested for conventional flame retardancy, mechanical properties, and UV resistance according to the following standards. The test results are shown in Table 1.Figure 5 , Figure 6 .

[0071] Flame retardant performance: Limiting oxygen index (LOI) test was conducted according to GB / T 2406.2-2009; vertical burning test was conducted according to GB / T2408-2021.

[0072] A 100mm × 100mm × 3mm sample was prepared according to ASTM ISO 5660 for cone calorimetry testing.

[0073] Mechanical properties: Tensile strength was tested according to GB / T 2567-2021 standard.

[0074] UV resistance performance: UV resistance was tested according to GB / T 2410–2008.

[0075] Table 1

[0076] Table 1 presents the flame retardant, mechanical, and UV resistance data for Examples 1 to 8 and Comparative Examples 1 to 3. The data in the table show that in Examples 1 to 8, the flame retardant rating of the composite material gradually increases with the increase of the amount of phosphorus-nitrogen-silicon composite flame retardant STLCP. Comparative Example 1 has no rating because no flame retardant was added. Examples 1, 2, 6, and 7 reach the V-1 level, while Examples 3, 4, 5, 8, and Comparative Example 2 all reach the V-0 level. This indicates that the introduction of the flame retardant significantly improves the flame retardant performance of the epoxy resin. The novel phosphorus-nitrogen-silicon flame retardant designed in this invention can significantly reduce the total heat release of epoxy resin. This characteristic greatly enhances the safety of the material in fire scenarios, laying a solid foundation for its application. Compared with Comparative Example 1, the mechanical properties of the embodiment have a significant advantage. The reason for this is that there is an interaction between the unique structure of the flame retardant and the epoxy resin matrix. This interaction can effectively optimize the internal bonding state, thereby enhancing the mechanical properties of the composite material and making it more competitive in mechanical performance. However, excessive addition will lead to a decrease in the mechanical properties of EP. Regarding UV resistance, the UPF values ​​of Examples 1 to 8 were significantly higher than those of Comparative Example 1, with Example 2 showing a significantly better performance than the other comparative examples. This indicates that the novel phosphorus-nitrogen-silicon flame retardant STLCP exhibits optimal UV resistance at low addition levels, while excessive addition may lead to a decrease in the UV resistance of the epoxy resin composite material.

[0077] Figure 4 shows digital photographs of Examples 1 to 3 and Comparative Examples 1 to 3. As can be clearly observed from the figures, although the composite materials with added flame retardants exhibit some color change, they still maintain a certain degree of transparency. It should be noted that the background patterns and text in the figures are only used to illustrate the transparent properties of the composite materials and have no other meaning.

[0078] Obviously, the foregoing embodiments of the present invention are merely illustrative examples to clearly present the core content of the invention and are not intended to strictly limit the specific implementation of the invention. For those skilled in the art, after fully understanding the above description, many different innovative variations can be derived. Due to the diversity of practical application scenarios and research and development ideas, it is impossible to list all possible implementation methods in detail here. However, it should be clarified that any significant changes that are reasonably extended or derived from the technical solution of the present invention and that can intuitively reflect the technical principles and innovative value of the present invention still fall within the protection scope of the present invention and are protected by patent and other intellectual property laws, in order to encourage technological innovation and reasonable expansion of applications.

Claims

1. A multifunctional flame retardant, characterized in that, The multifunctional flame retardant is prepared by reacting tert-butyldimethylchlorosilane with eugenol to obtain a primary intermediate; reacting the primary intermediate with an amino-containing compound to form a secondary intermediate with a Schiff base structure; and reacting the secondary intermediate with an organophosphorus reagent to prepare the target flame retardant.

2. The multifunctional flame retardant according to claim 1, characterized in that, The steps for synthesizing the multifunctional flame retardant are as follows: (1) Tert-butyldimethylchlorosilane reacts with eugenol in the presence of triethylamine via a nucleophilic substitution reaction to obtain a primary intermediate product; (2) The primary intermediate product and the amino compound form a secondary intermediate product with a Schiff base structure through a condensation reaction; (3) The secondary intermediate product and the organophosphorus reagent are reacted by addition reaction to obtain a multifunctional flame retardant.

3. The multifunctional flame retardant according to claim 2, characterized in that, In step (1), the molar ratio of eugenol, triethylamine and tert-butyldimethylchlorosilane is 0.05-0.1:0.05-0.01:0.05-0.1, the reaction temperature is 65-70℃, and the reaction time is 10-12h.

4. The multifunctional flame retardant according to claim 2, characterized in that, In step (2), the amino compounds are: 4,4'-diaminodiphenyl sulfone, chitosan, and p-phenylenediamine.

5. The multifunctional flame retardant according to claim 2, characterized in that, In step (2), the molar ratio of the primary intermediate to the amine compound is 0.07-0.014:0.5-1.0, the reaction temperature is 60-70℃, and the reaction time is 20-24h.

6. The multifunctional flame retardant according to claim 2, characterized in that, In step (3), the organophosphorus reagent is: diethyl phosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenyl phosphate.

7. The multifunctional flame retardant according to claim 2, characterized in that, In step (3), the molar ratio of the secondary intermediate product to the organophosphorus reagent is 0.05-0.1:0.1-0.2, the reaction temperature is 90-100℃, and the reaction time is 6-8h.

8. The application of a multifunctional flame retardant according to any one of claims 1-7, characterized in that, The flame retardant is used for flame retardant modification of epoxy resin.

9. The application of the multifunctional flame retardant according to claim 8, characterized in that, The flame-retardant modification method for the epoxy resin has the following steps: (a) Preheat the epoxy resin to a molten state to form a uniform epoxy resin solution; add the multifunctional flame retardant as described in claim 1 to the epoxy resin solution and stir until completely dispersed; (b) After adding the curing agent to step (a), continue stirring to form a homogeneous mixture; (c) After injecting the mixture into the preheated mold, place it in a vacuum drying oven to complete the curing process and obtain flame-retardant modified epoxy resin.

10. The application of the multifunctional flame retardant according to claim 9, characterized in that, The flame retardant has a mass percentage of 1-6 wt% in the epoxy resin; the stirring time is not less than 120 minutes; the curing agent is 4,4'-diaminodiphenylmethane, and the amount added is 25% of the resin mass.

Citation Information

Cited By

  • A2-grade flame-retardant aluminum-plastic panel core material and preparation method thereof

    CN121406040A